A gas humidity control composite honeycomb material and preparation method thereof
By intermittent coating on the honeycomb substrate surface of the honeycomb hygroscopic material, functional coating is formed, which solves the problem of degradation of the mechanical properties and moisture absorption ability of the material under changes in humidity, and achieves the long-term stability and efficient moisture absorption effect of the material.
Patent Information
- Application Number
- CN202410972537.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-19
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-07-19
AI Technical Summary
After the use time of honeycomb hygroscopic materials is extended, their mechanical properties and hygroscopic ability will decrease due to changes in humidity, which will affect the service life of the product.
The composite honeycomb material is controlled by gas humidity, and the functional coating is formed by intermittent coating on the surface of the honeycomb substrate, including hygroscopic materials and inorganic components, and the area ratio of the coating is regulated, and the functional coating area and blank areas are distributed at intervals to achieve effective stress release and gas diffusion.
It effectively maintains the moisture absorption ability and structural stability of honeycomb hygroscopic materials, extends the service life of the product, and improves the stability of mechanical properties.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of advanced environmentally friendly materials and more specifically relates to a gas humidity control composite honeycomb material and a preparation method thereof. Background Art
[0002] Honeycomb hygroscopic material is a new type of material with special structure and function. Its inspiration usually comes from the honeycomb structure in nature, which is famous for its light weight and large specific surface area.
[0003] Honeycomb hygroscopic materials usually have a highly porous structure, which provides them with a large surface area, thus helping to improve their hygroscopic capacity; they mainly rely on the porous structure to capture and retain water to achieve the hygroscopic function. Generally speaking, honeycomb hygroscopic materials can be prepared by a variety of methods, including chemical vapor deposition, sol-gel method and template method; during the preparation process, the material selection can include natural or synthetic polymers, metal organic framework materials, aerogels, etc.
[0004] However, it now appears that the durability of honeycomb hygroscopic materials may be a problem. Specifically, as the use time increases, the frequent humidity changes in the material itself will cause its mechanical properties and hygroscopic capacity to decrease. Therefore, how to maintain its hygroscopic capacity and keep the structure stable is one of the technical problems that technical personnel in this field still need to overcome. Summary of the invention
[0005] The technical problem to be solved by the present invention is that for honeycomb hygroscopic materials, as the use time increases, the frequent humidity changes of the material itself will lead to a decrease in its mechanical properties and hygroscopic capacity, thereby affecting the service life of the product. A gas humidity controlling composite honeycomb material and a preparation method thereof are provided.
[0006] The object of the present invention is to provide a composite honeycomb material for controlling gas humidity.
[0007] Another object of the present invention is to provide a method for preparing a gas humidity controlled composite honeycomb material.
[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0009] A gas humidity control composite honeycomb material, comprising a honeycomb substrate, and a functional coating on the surface of the honeycomb substrate;
[0010] Wherein, the honeycomb matrix is made of glass fiber mat or ceramic fiber mat;
[0011] The functional coating includes a hygroscopic material and an inorganic component;
[0012] The mass ratio between the hygroscopic material and the inorganic component is 1:(0.4-1);
[0013] The hygroscopic material is selected from any two of molecular sieves, silica gel, metal organic framework materials or polymer hygroscopic materials;
[0014] The inorganic component is selected from any one of silica sol, alumina sol and pseudo-boehmite;
[0015] Moreover, the functional coating is intermittently distributed on the surface of the honeycomb substrate to form functional coating areas and blank areas on the surface of the honeycomb substrate; the intermittent distribution is: the functional coating areas and the blank areas are distributed at intervals; wherein the area ratio of the functional coating areas to the blank areas is (2.0-2.2):1.
[0016] For the material of honeycomb structure, the stability of the overall structure can be guaranteed based on the honeycomb structure. However, the inventors found that if it is used as the substrate of hygroscopic material and the hygroscopic material is coated on the surface of the honeycomb structure, if the coating is full coating, during the humidity change process, as the hygroscopic and drying processes are alternately carried out, the volume of the hygroscopic material on the surface of the honeycomb material may change, thereby causing the internal stress to change. In this way, stress concentration is likely to occur at the corners of the honeycomb material. As the service life continues to increase, the repeated changes in stress will cause the mechanical properties here to be challenged. In addition, the release of stress is relatively difficult for honeycomb materials with relatively stable structures, especially the stress release at the corners, which will be more difficult. In the long run, it is also easy to weaken the bonding force between the surface coating and the substrate, resulting in the gradual detachment of the functional layer.
[0017] The above technical scheme forms a functional coating on the surface of the honeycomb substrate by intermittently coating the honeycomb substrate. Specifically, the functional coating area and the blank area are distributed at intervals, and the area ratio of the functional coating area and the blank area is regulated. Such an arrangement can make the stress generation in the functional coating area and the blank area also alternate during the use of the product. Mainly refers to that the blank area is not easy to generate stress, and it can serve as a buffer zone for stress release in the functional coating area, thereby effectively releasing the internal stress. In addition, as a honeycomb structure, the existence of the blank area can be beneficial to the diffusion of gas. Combined with the functional coating area, it can make the diffused humid gas be evenly adsorbed in the overall honeycomb structure, avoiding local excessive adsorption and causing local stress concentration.
[0018] Preferably, in the functional coating area, the functional coating is distributed in an island shape on the surface of the honeycomb substrate.
[0019] The inventors have discovered that, in actual use, the moisture absorption process of the gas in the functional coating area is essentially an adsorption process with the functional groups of the active substances in the functional coating layer or its pore structure. If the functional coating area is coated continuously, the coating in the functional coating area has a large cohesive force and it is difficult to form effective pores. In addition, its functional groups also form strong hydrogen bonds with each other and are difficult to expose. It can be said that most of the functional substances do not actually exert a moisture absorption effect. On the contrary, if an island distribution is carried out, the functional layer can be effectively wetted and spread on the surface of the substrate. On the one hand, during the drying process, due to the evaporation of solvents such as water, it is easier to form abundant pores. At the same time, the active components are also easy to fully spread and wet on the surface, thereby exposing the active functional groups. It can be said that a smaller coating amount can obtain the same or greater moisture absorption capacity.
[0020] Preferably, the surface density of the glass fiber felt or ceramic fiber felt is 30-50 g / ㎡.
[0021] Preferably, the surface density of the functional coating on the surface of the honeycomb substrate is 8-10 g / ㎡.
[0022] Preferably, the polymer hygroscopic material is selected from any one of polyvinyl alcohol and polyethylene glycol.
[0023] Preferably, in the functional coating area, there is a coupling agent between the functional coating and the honeycomb substrate;
[0024] The coupling agent is selected from any one of silane coupling agent KH-550, silane coupling agent KH-560 or silane coupling agent KH-570.
[0025] A method for preparing a gas humidity control composite honeycomb material, the specific preparation steps comprising:
[0026] The flat fiber substrate is coated with a hygroscopic material slurry on the functional coating area in a manner of spacing the functional coating area and the blank area, and then pressed into shape to obtain a corrugated fiber substrate coated with the hygroscopic material;
[0027] Another flat fiber substrate is coated with hygroscopic material slurry in the functional coating area in a manner of spacing the functional coating area and the blank area, and then laminated with the corrugated fiber substrate coated with the hygroscopic material. After drying and heat treatment, a composite honeycomb material is obtained.
[0028] Preferably, the coating hygroscopic material slurry comprises:
[0029] The flat fiber matrix is arranged in a manner of spacing the functional coating area and the blank area, the blank area is covered, the functional coating area is exposed, and then a functional coating is formed in the functional coating area by spraying, so as to form an island-shaped functional coating in the functional coating area.
[0030] Preferably, the coating hygroscopic material slurry comprises:
[0031] The flat fiber matrix is arranged in a manner of spacing the functional coating area and the blank area, the blank area is covered, the functional coating area is exposed, and then a coupling agent solution is sprayed on the functional coating area. After drying, the functional coating area is sprayed again to form a functional coating, so as to form an island-shaped distributed functional coating in the functional coating area. DETAILED DESCRIPTION
[0032] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0033] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0034] Example 1
[0035] The flat fiber matrix is arranged in a manner of spacing the functional coating area and the blank area, and the blank area is covered to expose the functional coating area, and the area ratio of the functional coating area to the blank area is 2.0:1; specifically, the blank area is pasted with an adhesive tape to cover the blank area, and then a coupling agent solution is sprayed on the functional coating area, wherein the coupling agent solution is a mixture of a coupling agent and an ethanol solution with a mass fraction of 60% in a mass ratio of 1:10; when spraying the coupling agent solution, the amount of the coupling agent in the spraying area is controlled to be 25mL / m 2 After drying, spraying the hygroscopic material slurry on the functional coating area to form an island-shaped functional coating in the functional coating area, and then pressing and molding at a temperature of 160° C. to obtain a corrugated fiber matrix coated with the hygroscopic material;
[0036] Another flat fiber matrix is placed in a manner of spacing the functional coating area and the blank area, and the blank area is covered to expose the functional coating area, and the area ratio of the functional coating area to the blank area is 2.0:1; specifically, the blank area is pasted with an adhesive tape to cover the blank area, and then a coupling agent solution is sprayed on the functional coating area, wherein the coupling agent solution is a mixture of a coupling agent and an ethanol solution with a mass fraction of 60% in a mass ratio of 1:10; when spraying the coupling agent solution, the amount of coupling agent in the spraying area is controlled to be 25mL / m 2 After drying, spraying the hygroscopic material slurry on the functional coating area to form an island-shaped functional coating in the functional coating area, and then laminating it with the corrugated fiber substrate coated with the hygroscopic material, and after drying, heat treating it at a temperature of 280° C. for 2 hours to obtain a composite honeycomb material;
[0037] The flat fiber matrix is made of glass fiber felt or ceramic fiber felt, and the surface density of the glass fiber felt or ceramic fiber felt is 30g / ㎡;
[0038] The surface density of the functional coating on the surface of the honeycomb substrate is 8 g / ㎡;
[0039] The coupling agent is selected from silane coupling agent KH-550;
[0040] The hygroscopic material slurry includes raw materials in the following mass ratio: the mass ratio between the hygroscopic material and the inorganic component is 1:0.4; in addition, it also includes water 6 times the mass of the hygroscopic material;
[0041] The hygroscopic material is selected from 4A molecular sieve;
[0042] The inorganic component is selected from silica sol with a mass fraction of 40%;
[0043] The thickness of the flat fiber matrix is 1.5 mm, and the total thickness of the composite honeycomb material is 15 mm.
[0044] Example 2
[0045] The flat fiber matrix is arranged in a manner of spacing the functional coating area and the blank area, and the blank area is covered to expose the functional coating area, and the area ratio of the functional coating area to the blank area is 2.1:1; specifically, the blank area is pasted with an adhesive tape to cover the blank area, and then a coupling agent solution is sprayed on the functional coating area, wherein the coupling agent solution is a mixture of a coupling agent and an ethanol solution with a mass fraction of 60% in a mass ratio of 1:10; when spraying the coupling agent solution, the amount of the coupling agent in the spraying area is controlled to be 25 mL / m2 After drying, spraying the hygroscopic material slurry on the functional coating area to form an island-shaped functional coating in the functional coating area, and then pressing and molding at a temperature of 180° C. to obtain a corrugated fiber matrix coated with the hygroscopic material;
[0046] Another flat fiber matrix is placed in a manner of spacing the functional coating area and the blank area, and the blank area is covered to expose the functional coating area, and the area ratio of the functional coating area to the blank area is 2.1:1; specifically, the blank area is pasted with an adhesive tape to cover the blank area, and then a coupling agent solution is sprayed on the functional coating area, wherein the coupling agent solution is a mixture of a coupling agent and an ethanol solution with a mass fraction of 60% in a mass ratio of 1:10; when spraying the coupling agent solution, the amount of coupling agent in the spraying area is controlled to be 25mL / m 2 After drying, spraying the hygroscopic material slurry on the functional coating area to form an island-shaped functional coating in the functional coating area, and then laminating it with the corrugated fiber substrate coated with the hygroscopic material, and after drying, heat treating it at a temperature of 290° C. for 2 hours to obtain a composite honeycomb material;
[0047] The flat fiber matrix is made of glass fiber felt or ceramic fiber felt, and the surface density of the glass fiber felt or ceramic fiber felt is 40g / ㎡;
[0048] The surface density of the functional coating on the surface of the honeycomb substrate is 9 g / ㎡;
[0049] The coupling agent is selected from silane coupling agent KH-560;
[0050] The hygroscopic material slurry includes raw materials in the following mass ratio: the mass ratio between the hygroscopic material and the inorganic component is 1:0.8; in addition, it also includes water 6 times the mass of the hygroscopic material;
[0051] The hygroscopic material is selected from silica gel;
[0052] The inorganic component is selected from aluminum sol with a mass fraction of 35%;
[0053] The thickness of the flat fiber matrix is 1.5 mm, and the total thickness of the composite honeycomb material is 15 mm.
[0054] Example 3
[0055] The flat fiber matrix is arranged in a manner of spacing the functional coating area and the blank area, and the blank area is covered to expose the functional coating area, and the area ratio of the functional coating area to the blank area is 2.2:1; specifically, the blank area is pasted with an adhesive tape to cover the blank area, and then a coupling agent solution is sprayed on the functional coating area, wherein the coupling agent solution is a mixture of a coupling agent and an ethanol solution with a mass fraction of 60% in a mass ratio of 1:10; when spraying the coupling agent solution, the amount of the coupling agent in the spraying area is controlled to be 25mL / m 2 After drying, spraying the hygroscopic material slurry on the functional coating area to form an island-shaped functional coating in the functional coating area, and then pressing and molding at a temperature of 220° C. to obtain a corrugated fiber matrix coated with the hygroscopic material;
[0056] Another flat fiber matrix is placed in a manner of spacing the functional coating area and the blank area, and the blank area is covered to expose the functional coating area, and the area ratio of the functional coating area to the blank area is 2.2:1; specifically, the blank area is pasted with an adhesive tape to cover the blank area, and then a coupling agent solution is sprayed on the functional coating area, wherein the coupling agent solution is a mixture of a coupling agent and an ethanol solution with a mass fraction of 60% in a mass ratio of 1:10; when spraying the coupling agent solution, the amount of the coupling agent in the spraying area is controlled to be 25mL / m 2 After drying, spraying the hygroscopic material slurry on the functional coating area to form an island-shaped functional coating in the functional coating area, and then laminating the functional coating with the corrugated fiber substrate coated with the hygroscopic material, drying, and heat treating at 300° C. for 2 hours to obtain a composite honeycomb material;
[0057] The flat fiber matrix is made of glass fiber felt or ceramic fiber felt, and the surface density of the glass fiber felt or ceramic fiber felt is 50g / ㎡;
[0058] The surface density of the functional coating on the surface of the honeycomb substrate is 10 g / ㎡;
[0059] The coupling agent is selected from silane coupling agent KH-570;
[0060] The hygroscopic material slurry includes raw materials in the following mass ratios: the mass ratio between the hygroscopic material and the inorganic component is 1:1; in addition, it also includes water 6 times the mass of the hygroscopic material;
[0061] The hygroscopic material is selected from metal organic framework materials (aluminum fumarate);
[0062] The inorganic component is selected from pseudo-boehmite;
[0063] The thickness of the flat fiber matrix is 1.5 mm, and the total thickness of the composite honeycomb material is 15 mm.
[0064] Example 4
[0065] The present embodiment is different from the embodiment 1 in that an ethanol solution of the same mass and with a mass fraction of 60% is used to replace the coupling agent solution, and the other conditions remain unchanged.
[0066] Comparative Example 1
[0067] Compared with Example 1, this comparative example differs in that roller coating is used instead of spraying, specifically:
[0068] The flat fiber matrix is arranged in a manner of spacing the functional coating area and the blank area, and the blank area is covered to expose the functional coating area, and the area ratio of the functional coating area to the blank area is 2.0:1; specifically, the blank area is pasted with an adhesive tape to cover the blank area, and then a coupling agent solution is applied to the functional coating area by roller coating, wherein the coupling agent solution is a mixture of a coupling agent and an ethanol solution with a mass fraction of 60% in a mass ratio of 1:10; when the coupling agent solution is applied by roller coating, the amount of the coupling agent in the roller coating area is controlled to be 25 mL / m 2 After drying, the functional coating area is coated with a hygroscopic material slurry by roller coating to form a continuously distributed functional coating in the functional coating area, and then pressed at a temperature of 160° C. to obtain a corrugated fiber substrate coated with a hygroscopic material;
[0069] Another flat fiber matrix is placed in a manner of spacing the functional coating area and the blank area, and the blank area is covered to expose the functional coating area, and the area ratio of the functional coating area to the blank area is 2.0:1; specifically, the blank area is pasted with an adhesive tape to cover the blank area, and then a coupling agent solution is applied to the functional coating area by roller coating, wherein the coupling agent solution is a mixture of a coupling agent and an ethanol solution with a mass fraction of 60% in a mass ratio of 1:10; when the coupling agent solution is applied by roller coating, the amount of the coupling agent in the roller coating area is controlled to be 25 mL / m 2 After drying, the hygroscopic material slurry is roll-coated on the functional coating area to form a continuously distributed functional coating in the functional coating area, and then the hygroscopic material is laminated to the corrugated fiber substrate coated with the hygroscopic material. After drying, the composite honeycomb material is obtained after heat treatment at 280°C for 2 hours.
[0070] The rest of the conditions remain unchanged.
[0071] Comparative Example 2
[0072] The difference between this comparative example and Example 1 is that no blank area is set, and other conditions remain unchanged.
[0073] Comparative Example 3
[0074] The difference between this comparative example and Example 1 is that the ratio of the area of the functional coating area to the area of the blank area is 1.8:1, and the other conditions remain unchanged.
[0075] The performance tests were performed on the products obtained in Examples 1-4 and Comparative Examples 1-3. The specific test methods and test results are as follows:
[0076] Plane tensile strength test:
[0077] Samples of the products of each embodiment or comparative example were taken, and the sample size was 60mm×60mm. The plane tensile strength of the products before and after moisture absorption was tested respectively. The test was carried out on an INSTRON 8801 test machine in accordance with the ASTM C297 "Sandwich Structure Planar Tensile Strength Test Method" standard. During the test, a tensile load was applied at a loading speed of 0.5mm / min until the maximum load was reached and the load decreased by 30% from the maximum load. The detailed test results are shown in Table 1.
[0078] The specific treatment process of the sample after moisture absorption is as follows: after continuous treatment for 14 days at a temperature of 75°C and a relative humidity of 85%, the sample is taken out and dried to constant weight at a temperature of 100°C. After the dried sample is subjected to such moisture absorption-drying cycle for 10 times, the moisture absorption treatment is completed.
[0079] Plane tensile strength before moisture absorption / MPa Planar tensile strength after moisture absorption / MPa Example 1 1.26 1.19 Example 2 1.28 1.21 Example 3 1.31 1.20 Example 4 1.21 1.08 Comparative Example 1 1.29 1.13 Comparative Example 2 1.34 1.05 Comparative Example 3 1.15 1.01
[0080] It can be seen from the test results in Table 1 that the product obtained by the present invention not only has beneficial initial mechanical properties, but also, after a long period of moisture absorption and drying cycles, its mechanical properties still remain at a high level.
[0081] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A gas humidity control composite honeycomb material, characterized in that: It includes a honeycomb substrate and a functional coating on the surface of the honeycomb substrate; Wherein, the honeycomb matrix is made of glass fiber mat or ceramic fiber mat; The functional coating includes a hygroscopic material and an inorganic component; The mass ratio between the hygroscopic material and the inorganic component is 1:(0.4-1); The hygroscopic material is selected from any two of molecular sieves, silica gel, metal organic framework materials or polymer hygroscopic materials; The inorganic component is selected from any one of silica sol, alumina sol and pseudo-boehmite; Moreover, the functional coating is intermittently distributed on the surface of the honeycomb substrate to form functional coating areas and blank areas on the surface of the honeycomb substrate; the intermittent distribution is: the functional coating areas and the blank areas are distributed at intervals; wherein the area ratio of the functional coating areas to the blank areas is (2.0-2.2):
1.
2. The gas humidity control composite honeycomb material according to claim 1, characterized in that: In the functional coating area, the functional coating is distributed in an island shape on the surface of the honeycomb substrate.
3. The gas humidity control composite honeycomb material according to claim 1, characterized in that: The surface density of the glass fiber felt or ceramic fiber felt is 30-50 g / ㎡.
4. The gas humidity control composite honeycomb material according to claim 1, characterized in that: The surface density of the functional coating on the surface of the honeycomb substrate is 8-10 g / ㎡.
5. The gas humidity control composite honeycomb material according to claim 1, characterized in that: The polymer hygroscopic material is selected from any one of polyvinyl alcohol and polyethylene glycol.
6. The gas humidity control composite honeycomb material according to claim 1, characterized in that: In the functional coating area, there is a coupling agent between the functional coating and the honeycomb substrate; The coupling agent is selected from any one of silane coupling agent KH-550, silane coupling agent KH-560 or silane coupling agent KH-570.
7. A method for preparing a gas humidity control composite honeycomb material according to any one of claims 1 to 6, characterized in that: The specific preparation steps include: The flat fiber substrate is coated with a hygroscopic material slurry on the functional coating area in a manner of spacing the functional coating area and the blank area, and then pressed into shape to obtain a corrugated fiber substrate coated with the hygroscopic material; Another flat fiber substrate is coated with hygroscopic material slurry in the functional coating area in a manner of spacing the functional coating area and the blank area, and then laminated with the corrugated fiber substrate coated with the hygroscopic material. After drying and heat treatment, a composite honeycomb material is obtained.
8. The method for preparing a gas humidity control composite honeycomb material according to claim 7, characterized in that: The coating hygroscopic material slurry comprises: The flat fiber matrix is arranged in a manner of spacing the functional coating area and the blank area, the blank area is covered, the functional coating area is exposed, and then a functional coating is formed in the functional coating area by spraying, so as to form an island-shaped functional coating in the functional coating area.
9. The method for preparing a gas humidity control composite honeycomb material according to claim 8, characterized in that: The coating hygroscopic material slurry comprises: A flat fiber matrix is placed in a manner of spacing functional coating areas and blank areas, the blank areas are covered, the functional coating areas are exposed, and then a coupling agent solution is sprayed on the functional coating areas. After drying, the functional coating areas are sprayed again to form a functional coating, so as to form an island-shaped functional coating in the functional coating areas.
Citation Information
Patent Citations
Preparation method of long-acting humidity-controlling material
CN113005762A
Glass fiber air filtering material and application thereof
CN114618232A